In-vitro diffusion study of caffeine from microemulsion gel system containing grape seed oil - Sani Ega Priani; Dinnanda Yussepina Wulansari; Fitrianti Darusman (Pharmaciana, 2021)
Cellulite was identified by the orange-peel appearance of skin surface that presents in 80-90% of post-pubertal women. Caffeine and grape seed oil were known can be used as an anti-cellulite agent. Microemulsion systems are known could enhance the diffusion rate of drugs through the skin. This study was conducted to develop a microemulsion gel containing caffeine and grape seed oil and determine the effect of caffeine's in vitro diffusion profile. Microemulsion gel was prepared using tween 80 as a surfactant, glycerin as cosurfactant, viscolam mac 10 as a gelling agent. The preparations were evaluated by organoleptic, pH, viscosity, rheology, spreadability, globule size, and thermodynamic stability tests. In vitro diffusion tests were performed by Franz diffusion cell. The result showed that microemulsion containing 1 % of caffeine and 5% of grapeseed oil has good physical characteristics and stability with an average globule size 126 Â±17 nm. Microemulsion gel system could enhance the cumulative release amount of caffeine through synthetic membrane compared with gel system. Drug release kinetics of caffeine from microemulsion gel system follows the Higuchi model.